Deep phenotyping of 34,128 adult patients hospitalised with COVID-19 in an international network study - Edward Burn (Nature Portfolio, 2020)
Detailed knowledge of the characteristics of COVID-19 patients helps with public health planning. Here, the authors use routinely-collected data from seven databases in three countries to describe the characteristics of >30,000 patients admitted with COVID-19 and compare them with those admitted for influenza in previous years.